Extracellular vesicles promote the infection and pathogenicity of Japanese encephalitis virus - Junyao Xiong; Ling'en Yang; Xiaowei Nan; Shuo Zhu; Mengxue Yan; Shengxian Xiang; Luping Zhang; Qi Li; Chengjie Yang; Xugang Wang; Ning Wei; Huanchun Chen; et al. (Journal of Extracellular Vesicles)
Abstract Japanese encephalitis virus (JEV) is a neurotropic zoonotic pathogen that poses a serious threat to public health. Currently, there is no specific therapeutic agent available for JEV infection, primarily due to the complexity of its infection mechanism and pathogenesis. Extracellular vesicles (EVs) have been known to play an important role in viral infection, but their specific functions in JEV infection remain unknown. Here, ultracentrifugation in combination with density gradient centrifugation was conducted to purify EVs from JEV‐infected cells. The purified EVs were found to be infectious, with virions observed inside the EVs. Furthermore, our study showed the formation process of virion‐containing EVs both in vitro and in vivo, which involved the fusion of multivesicular bodies with the cell membrane, leading to the release of virion‐containing intraluminal vesicles into the extracellular space. Further studies revealed that EVs played a crucial role in JEV propagation by facilitating viral entry and assembly‐release. Furthermore, EVs assisted JEV in evading the neutralizing antibodies and promoted viral capability to cross the blood‐brain and placental barriers. Moreover, in vivo experiments demonstrated that EVs were beneficial for JEV infection and pathogenicity. Taken together, our findings highlight the significant contribution of EVs in JEV infection and provide valuable insights into JEV pathogenesis.